2009
DOI: 10.1039/b819292h
|View full text |Cite
|
Sign up to set email alerts
|

Ceramic membranes for separation of proteins and DNA through in situ growth of alumina nanofibres inside porous substrates

Abstract: Ceramic membranes were fabricated by in situ synthesis of alumina nanofibres in the pores of an alumina support as a separation layer, and exhibited a high permeation selectivity for bovine serum albumin relative to bovine hemoglobin (over 60 times) and can effectively retain DNA molecules at high fluxes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…There is a consensus that surface properties of BSA vary across the molecule giving rise to charge heterogeneity (Baier et al, 2011), along with hydrophobic and hydrophilic regions (Yoon et al, 1998). Consequently, morphological models of BSA needs simplification to certain degrees: it is described either as a globular ellipsoid of about 14 x 3.8 x 3.8 nm (Ke et al, 2009;Togashi et al, 2009), a heart-shaped solid with three different domains (Voros, 2004), or a flexible foldable polymer (Chiku et al, 2008). Among them, the ellipsoid model not only provides explicit size and geometry description of the protein molecule, but also offers a realistic means to characterise the adsorbed conformation in end-on (long axis perpendicular to collector surface) or side-on (short axis perpendicular to collector surface) (Yoon et al, 2003;Schrott et al, 2009).…”
Section: Double Pulse Column Experiments (Dpes)mentioning
confidence: 99%
“…There is a consensus that surface properties of BSA vary across the molecule giving rise to charge heterogeneity (Baier et al, 2011), along with hydrophobic and hydrophilic regions (Yoon et al, 1998). Consequently, morphological models of BSA needs simplification to certain degrees: it is described either as a globular ellipsoid of about 14 x 3.8 x 3.8 nm (Ke et al, 2009;Togashi et al, 2009), a heart-shaped solid with three different domains (Voros, 2004), or a flexible foldable polymer (Chiku et al, 2008). Among them, the ellipsoid model not only provides explicit size and geometry description of the protein molecule, but also offers a realistic means to characterise the adsorbed conformation in end-on (long axis perpendicular to collector surface) or side-on (short axis perpendicular to collector surface) (Yoon et al, 2003;Schrott et al, 2009).…”
Section: Double Pulse Column Experiments (Dpes)mentioning
confidence: 99%
“…Applications such as alumina membranes for juice processing [1], protein separation [2], and oil/water emulsion separation [3], titania membranes for wastewater processing [4], zirconia membranes for processing vegetable oil [5] and food [6], zeolites for the dehydration of organic solvents [7], cobalt silica membranes for ammonia separation from waste waters [8] and carbonized templated silica membranes for desalination [9] are some of many examples. Inorganic membranes have a very wide range of pore sizes from microfiltration to ultrafiltration to nanofiltration and even down to the sub-nanometer range depending on the materials of choice and synthesis conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have already indicated that the mesh-like structure formed from threads or fibers represents the most efficient structure for pressure-driven membrane-filtration processes [15][16][17][18][19][20]. Such a structure is able to achieve high selectivity while retaining extremely high filtration rates.…”
Section: Introductionmentioning
confidence: 99%